RECTAL MISOPROSTOL VS 15-METHYL PROSTAGLANDIN F2α FOR THE PREVENTION OF POST PARTUM HEMORRHAGE - Patil, Amrutha S. (Journal of Biomedical and Pharmaceutical Research, 2017)
1. To compare the efficacy and side effects of 400μg of rectal misoprostol with intramuscular 125μg PGF2α in prevention of postpartum haemorrhage. 2. To estimate amount of blood loss during the third stage and duration of third stage of labour in both groups.